Vox Populi? Citizen Alienation and the Political and Media Elite - Braw, E (2014)
Politicians and journalists rank at the bottom of public confidence surveys. This working paper attempts an explanation, and examines the potential consequences of such citizen distrust in the public institutions that -- de jure or de facto -- are supposed to represent them. Though there is, of course, no easy fix to the problem, this paper also presents several partial solutions.